Expected effects of the US tax reform on other countries: Global and local survey evidence - Dorine Boumans; Clemens Fuest; Carla Krolage; Klaus Wohlrabe (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The Tax Cuts and Jobs Act constitutes the largest change to the US tax system since the 1980s and thoroughly alters the way in which multinational companies are taxed. Current assessments on the reform's international impact vary widely. This article sheds light on the tax reform's expected effects on other countries. We first use representative German business survey data to analyze the impact of the reform on German firms. Many firms with substantial US revenues or capacities in the US intend to expand US investment in response to the reform, in particular large firms and manufacturing companies. The effects on investment in Germany are ambiguous: While some firms substitute between investment locations, others expand in both countries. We subsequently extend our analysis to a global level using worldwide survey data. The results suggest a negative impact on tax revenues and investment in countries with close economic ties to the US.
Keywords: H25; H32; D22; F23; E62; 330; US tax reform; Tax Cuts and Jobs Act; corporate tax; firm responses; survey; Germany